Lanthanide Complexes with 4, 4′‐Bis(2‐sulfonatostyryl)‐biphenyl: Crystal Structures and Luminescence Properties. Issue 4 (18th January 2022) - Mikhalyova, Elena A.; Zeller, Matthias; Goreshnik, Evgeny A.; Jasinski, Jerry P.; Butcher, Raymond J.; Nelyubina, Yulia V.; Hunter, Jordan L.; Sedykh, Alexander E.; Shishkina, Svitlana V.; Müller‐Buschbaum, Klaus; Eremenko, Igor L.; Addison, Anthony W.; et al.
Abstract: A series of new tris(pyrazolyl)borate (Tp − ) and tris(2‐pyridylpyrazolyl)borate (Tp Py− ) Eu 3+, Gd 3+, Tb 3+ and Dy 3+ complexes with the dianionic ligand 4, 4′‐bis(2‐sulfonatostyryl)biphenyl (Ssp 2−, a widely used fluorescent whitener) were synthesized and their luminescence properties were studied. The Gd 3+, Tb 3+ and Dy 3+ compounds possess only ligand‐centered emission, arising from the Ssp 2− ligand, with quantum yields of up to 60 %. While the emission centers in these complexes are similar, the positions of the luminescence maxima, the emission quantum yields, and the lifetimes change in the order [(Tp2 Ln)2 Ssp]<[(Tp Py LnSsp)2 ]<[Ln2 Ssp3 ]n . Among the complexes studied, Eu 3+ ‐centered emission was observed for only [(Tp2 Eu)2 Ssp]. In this compound, Tp − plays the role of an antenna ligand for Eu 3+ ‐radiation, though the quantum yield is only 5 %. Abstract : Although the emission centers in the Tb 3+, Gd 3+, and Dy 3+ complexes described are similar, the positions of the luminescence maxima, the emission quantum yields, and the lifetimes change consistently in the order [(Tp2 Ln)2 Ssp]<[(Tp Py LnSsp)2 ]<[Ln2 Ssp3 ]n .